2023
DOI: 10.1002/hsr2.1412
|View full text |Cite
|
Sign up to set email alerts
|

The normal value and influencing factors of shear wave elastography in healthy tibial nerves: A cross‐sectional study

Abstract: Background and Aims: Shear wave elastography is a potential method for evaluating peripheral neuropathy, but lacking reference values. The aim of this study was to measure tibial nerve stiffness in healthy individuals using shear wave elastography and to investigate the influencing factors of tibial nerve stiffness.Methods: Shear wave elastography of bilateral tibial nerves was performed in 50 healthy individuals 4 cm proximal to the medial malleolus. Mean shear modulus data of tibial nerves were obtained and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…One study measuring the shear wave velocity of the median and tibial nerves observed that male participants had significantly higher shear wave velocities for the median nerve than female participants, but no differences were observed regarding the tibial nerve [ 43 ]. Similar findings were reported in another study [ 42 ] that observed no differences in the stiffness of the tibial nerve between male and female participants. Conflicting results have been reported on the effect of ageing on nerve shear wave velocity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…One study measuring the shear wave velocity of the median and tibial nerves observed that male participants had significantly higher shear wave velocities for the median nerve than female participants, but no differences were observed regarding the tibial nerve [ 43 ]. Similar findings were reported in another study [ 42 ] that observed no differences in the stiffness of the tibial nerve between male and female participants. Conflicting results have been reported on the effect of ageing on nerve shear wave velocity.…”
Section: Discussionsupporting
confidence: 91%
“…The reported values show high variability for both the tibial (range, 2.3 to 9.1 m/s) and the sciatic nerves (range, 1.9 to 9.9 m/s). Most of the studies included young adults, while three studies [ 39 , 42 ] compared nerve shear wave velocity between younger and older participants. Hirata et al [ 39 ] showed significantly lower sciatic nerve shear wave velocities in older adults than in younger adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation